Output-Based Aid and Energy : What Have We Learned So Far? - Kumar, Geeta; Mumssen, Yogita (World Bank, Washington, DC, 2012)
Worldwide, nearly 1.4 billion people live without access to electricity and nearly 2.7 billion people use traditional biomass fuels for cooking. One challenge to increasing reliable energy access for the poor is their limited ability to pay the up-front connection fees for electricity and natural gas. Output-based aid (OBA) approaches in which subsidy payments are linked to predefined outputs, such as installation of a working household connection or solar home system offers a potential solution that has increased energy access for more than 6.8 million poor beneficiaries. A recent World Bank review of OBA concludes that there is a case to adopt OBA more widely, where there is an enabling environment (Mumssen, Johannes, and Kumar, 2010). This note discusses lessons learned and best practices in implementing OBA in the energy sector.